Enhanced thermoelectric performance of Sn-doped Cu3SbS4. Issue 31 (1st August 2018) - Chen, Kan; Di Paola, Cono; Du, Baoli; Zhang, Ruizhi; Laricchia, Savio; Bonini, Nicola; Weber, Cedric; Abrahams, Isaac; Yan, Haixue; Reece, Mike
Abstract : Enhanced thermoelectric performance of Cu3 SbS4 with fine microstructure and optimized carrier concentration by Sn-doping. Abstract : Cu3 SbS4 is an earth-abundant and low-cost alternative thermoelectric material for medium temperature applications. Tin doping into Cu3 SbS4 yields materials with high thermoelectric performance. The electronic structure of Sn-doped Cu3 SbS4 was studied using both hybrid density functional theory (DFT) and the quasi-particle self-consistent GW (QSGW) approach. A synthesis method involving mechanical alloying (MA) and spark plasma sintering (SPS) was employed to produce dense and single phase Cu3 SbS4 samples with very fine grain size. Previously unreported nano-scale twins on {112} planes were observed by transmission electron microscopy (TEM). All of the samples showed very low lattice thermal conductivity, which is attributed to their microstructures. Sn was found to substitute Sb successfully in Cu3 SbS4 and work effectively as an acceptor dopant, leading to an enhanced power factor. A maximum zT value of 0.72 at 623 K was achieved in Cu3 Sb1− x Sn x S4 ( x = 0.05), which is comparable to the Se analogue Cu3 SbSe4 .